PENGARUH PEMIKIRAN RASYID RIDHO TERHADAP PENAFSIRAN TAFSIR AT-TANWIR MUHAMMADIYAH: STUDI AYAT PUASA - Muhammad Abdullah (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2024)
The journal analyzes the influence of Rasyid Ridho's thoughts in the interpretation of the Quran known as "At Tanwir," especially concerning verses related to fasting. It explores Rasyid Ridho's contributions to Muhammadiyah's understanding of fasting in Islam, using textual analysis to delve into his interpretations of Quranic verses on fasting and their impact on fasting practices within the Muhammadiyah community. The research found similarities between Tafsir At-Tanwir and Al-Manar in their understanding of fasting, particularly in terminology, expectations/results in fasting, and the use of calculation methods. Overall, the study supports a deeper comprehension of Rasyid Ridho's role and influence within the context of Muhammadiyah's interpretation of the Quran, specifically in the practice of fasting